Dampak Media Sosial Terhadap Perubahan Perilaku Remaja Ketika Bersosialisasi - Triani, Sonia Nyoman; Niki, Novembra B; Paremm, Mahdalena Madeline; Margono, Rizky Pandu Keling; Geraldo, Jovee Charlie Caesar; Lian, Yohanes Pemandi (Universitas Pahlawan Tuanku Tambusai, 2024)
Social media has become an integral part of modern teenage life, influencing how they interact and socialize. This study aims to investigate the impact of social media on adolescent behavior changes in the context of socialization. Through qualitative approaches and surveys involving adolescents aged 15-18 years, this research explores how social media usage affects social behaviors, communication patterns, and their understanding of social norms. Findings indicate that social media provides a platform for adolescents to build and maintain social relationships on a broader scale, but also presents new challenges such as experiences of cyberbullying, negative influences from unhealthy content, and excessive use of time. In this context, adolescent social behavior can undergo significant changes, both positively and negatively. The study also identifies that communication patterns among adolescents have significantly shifted, with a preference for digital interaction sometimes displacing face-to-face interaction. Meanwhile, their understanding of social norms is often influenced by exposure to various viewpoints and values presented through social media. The research concludes that while social media offers significant benefits in facilitating social interaction and interpersonal connections, there is a need for awareness of the risks associated with uncontrolled use. The implications of these findings provide guidance for parents, educators, and policymakers to develop balanced approaches to social media use among adolescents, promoting responsible and positive usage within their social contexts.